The Effects of ESL Student‟s Attitude on Academic Writing Apprehensions and Academic Writing Challenges - Akhtar, Rubina; Hassan, Hanita; Saidalvi, Aminabibi (International Journal of Psychosocial Rehabilitation, 2020)
The main purpose of this study is to explore the effects of ESL first-year students’ attitudes on academic writing, writing apprehensions, and challenges of academic writing at Universiti Teknologi Malaysia (UTM). A total number of 27 students participated in this study. For the data collection, the Writing Apprehensions Test (WAT) was developed and adapted from a test designed by Daly & Miller (1975). The questionnaire items were divided into three categories: the first is on general students’ attitude towards academic writing, the second focuses on students’ academic writing apprehension, and the last is on academic writing challenges. The outcomes of this study indicate that academic challenges are the main cause for the students to be apprehensive towards writing. In addition, most importantly, students’ negative attitude towards academic writing results in a lack of interest in academic writing. However, the findings show that most students are aware of the importance of ESL writing and its requirements.